The Influence of Leadership Style, Work Commitment and Employee Attachment on Employee Performance at PT Ingco - Lyra Aulia; M. Chaerul Rizky; Aswan Waruwu (Utan Kayu Publishing, 2025)
This study aims to analyze the influence of leadership style, work commitment, and employee attachment on employee performance at PT INGCO. Employee performance is a key factor that determines the success of an organization in the face of increasingly competitive business competition. This type of research is quantitative research with a causal associative approach. The population in this study is all employees of PT INGCO which currently amounts to 85 employees, and the entire population is used as a research sample (saturated sampling). The data collection method used a questionnaire with a Likert scale, and the data analysis technique used was multiple linear regression analysis with the help of SPSS software. The results of the study showed that: (1) Leadership style had a positive and significant effect on employee performance with a calculated t value of 4.151 t table of 1.990 and a significance of 0.001 0.05, with a regression coefficient of 0.418 and Beta of 0.432 which was the most dominant influence; (2) Work commitment has no significant effect on employee performance with a calculated t value of 1.602 table 1.990 and a significance of 0.113 0.05; (3) Employee attachment has a positive and significant effect on employee performance with a calculated t-value of 2.197 t table of 1.990 and significance 0.031 0.05, with a regression coefficient of 0.288; (4) Simultaneously, leadership style, work commitment, and employee attachment have a significant effect on employee performance with an F value of 61.349 F table 2.72 and a significance of 0.001. A determination coefficient value (R²) of 0.694 indicates that 69.4% of employee performance variations can be explained by all three independent variables, while the remaining 30.6% are explained by other factors outside the study model